Factors contributing to the high performance of english language amongst students in Sekolah Kebangsaan Teris Hulu Terengganu, Terengganu / Nor Aizah Abd. Manaf - Abd. Manaf, Nor Aizah (2002)
The general aim of this study is to determine factors that contribute to high performance of English Language amongst students in Sekolah Kebangsaan Teris, Hulu Terengganu, Terengganu in the UPSR 1999 and 2000. The factors investigated were educational setting (school), school input and also teaching and learning process. A questionnaire developed by the reseacher was distributed to 20 students who had left Sekolah Kebangsaan Teris and they are now in the secondary school, which is Sekolah Menengah Matang, Hulu Terengganu. All the students obtained ‘B’ and ‘C’ grade for their English Language in the UPSR. The following were the major findings of the study: 1. The students perceived their school as ‘successful’ and ‘most successful’ in developing good relationship between teachers and students. 2. Students also indicated they 'agree' and 'strongly agree' that the classroom environment motivates them to learn English . 3. Teacher’s teaching style also contributed to students’ high performance in English. 4. The study also showed that the process of teaching and learning also contributed to students’ high performance in English. The findings from this study suggested that educational setting, school input, the process of teaching and learning contributed to high performance of English Language amongst students.